1990
DOI: 10.1177/38.3.1689344
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for preparing cryostat sections of undecalcified bone for multiple uses.

Abstract: We developed a technique that permits the use ofserial 5cctiwis (7-20 .tm) from a single fixed piece of bone tissue for immunofluorescence, measurement of fluorescent bone labels, enzyme histochemistry, and general staining. This technique combines modifications ofpreviously established methods with perfusion ofthe polymer polyvinylpyrrollidone (PVP) to improve sectioning, and produces reliable sections with good preservation of both hard and soft tissues. The combination of techniques from several workers, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In particular, decalcification may affect the degree of staining, since some materials are easily lost and/or dislocated from the original sites during the process. In order to avoid the disadvantage associated with fixation and decalcification, a number of attempts have been made to obtain unfixed and non-decalcified sections of calcified tissue (Hammarstrom 1986;Hill and Elde 1990;Fink 1992;McElroy et al 1993;Shimada and Watanabe 1995). However, most of those previous sections could be improved, because the sections were too thick and because the sizes of the available samples were limited to small ones.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, decalcification may affect the degree of staining, since some materials are easily lost and/or dislocated from the original sites during the process. In order to avoid the disadvantage associated with fixation and decalcification, a number of attempts have been made to obtain unfixed and non-decalcified sections of calcified tissue (Hammarstrom 1986;Hill and Elde 1990;Fink 1992;McElroy et al 1993;Shimada and Watanabe 1995). However, most of those previous sections could be improved, because the sections were too thick and because the sizes of the available samples were limited to small ones.…”
Section: Introductionmentioning
confidence: 99%
“…mmunohistochemical studies have demonstrated a network of peptidergic nerve fibers in the skeleton [Bjurholm et al, 1989;Hill and Elde, 1990]. The close proximity between nerve endings and bone cells [Imai et al, 1997], and the increased density of skeletal nerve fibers in areas with high metabolic activity such as the growth plate [Hukkanen et al, 1993], growing antlers [Gray et al, 1992], and the callus of healing skeletal fractures [Madsen et al, 1998] have suggested that the signaling molecules in skeletal nerve fibers not only have sensory functions but may also participate in the control of bone cell activities [reviewed in Lerner et al, 2008].…”
mentioning
confidence: 99%
“…A superhard reusable knife made of a hardened tungsten steel permits cutting of hard tissues such as bone, dentine, and enamel (Van Noorden and Vogels 1986;Hill and Elde 1990;Haines 1992;McElroy et al 1993;Nakamura et al 1994). In order to achieve this, some refine-ments were made in the equipment.…”
Section: Discussionmentioning
confidence: 99%